Interaction of alpha-actinin and vinculin with actin: opposite effects on filament network formation. - Jockusch, B M (1981)
The interaction of actin filaments with two actin-associated proteins, alpha-actinin and vinculin (Mr 130,000 protein), was studied in vitro with viscometry and light and electron microscopy. Vinculin, like alpha-actinin, binds to F-actin, and the two proteins were found to have different effects on the formation of filament networks: alpha-actinin crosslinks individual filaments in a manner strongly dependent on temperature and acts as a spacer, whereas vinculin forms actin bundles that display a paracrystalline substructure. In viscometric assays, alpha-actinin mimics the effect of actin gelation factors, whereas vinculin acts as a gelation inhibitor. These findings imply complementary functions of these proteins in the regulation of cellular mobility.